LEGAL MECHANISMS SHAPING THE CONDITIONS FOR INTELLECTUAL MIGRATION IN UKRAINE - OLIINYK, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the regulatory and legal mechanisms that shape the conditions for intellectual migration in Ukraine. The relevance of the study is substantiated in the context of the growth in the scale of migration of highly qualified workers and the need to harmonize Ukrainian legislation with European standards. A content analysis of the Strategy of the State Migration Policy of Ukraine for the period until 2025 is conducted. The formed map of the keywords of the Strategy emphasizes that the document has a clearly expressed normative character. The focus is on the role of the government, ministries, the Verkhovna Rada, that is, the emphasis is on the institutional level of formation and implementation of migration policy. At the same time, concepts related to intellectual migration, talents, scientists, researchers, recognition of qualifications, etc. are absent or almost absent. It was determined that the current legal framework of Ukraine - the Law of Ukraine "On Immigration", the Law of Ukraine "On Employment of the Population", the Law of Ukraine "On the Legal Status of Foreigners and Stateless Persons", the Law of Ukraine "On Higher Education" - only partially covers the issues of academic and professional mobility, not providing comprehensive regulation of intellectual migration. A comparative analysis was conducted with Directive (EU) 2021/1883 and other acts of the European Union, which form a single regulatory framework for talent management, mobility and highly qualified employment. It was found that, unlike the EU, where the legal regulation of intellectual migration is considered as an element of economic and innovation policy, in Ukraine it is reduced mainly to issues of controlling migration flows. The need to develop a concept of state policy on intellectual mobility, adapt European directives to the national legal system and create institutional mechanisms to facilitate the return of highly qualified specialists is substantiated.
Keywords: migration; intellectual migration; regulatory and legal regulation; highly qualified workers; European Union; institutional mechanisms